Islamic finance and ESG: Panel analysis of sustainability in OIC countries - Mian Muhammad Ajmal Khan; Ayesha Munir (Priviet Social Sciences Journal, 2025)
This study investigates the relationship between Islamic finance development and environmental performance in ten Organisation of Islamic Cooperation (OIC) countries from 2010 to 2023, focusing on the moderating role of governance quality. Using the Environmental Performance Index (EPI) as a composite measure of sustainability, we employ fixed-effects panel regression models to test whether a higher share of Islamic finance in national banking sectors is associated with improved environmental outcomes and whether governance quality strengthens this relationship. Contrary to prevailing theoretical expectations, the results reveal a persistent and statistically significant negative association between the Islamic finance share and environmental performance across all model specifications. Governance quality shows a modest, positive direct effect on environmental performance, but fails to moderate the Islamic finance environment nexus in a statistically significant way. GDP per capita consistently negatively influences EPI scores, indicating a growth environment trade-off, while foreign direct investment remains insignificant. These findings challenge the assumption that Islamic finance is inherently aligned with environmental goals and highlight the need for targeted policy interventions, such as explicit environmental screening in Shariah governance, development of green Islamic finance products, and integrated sustainability mandates that the sector contributes meaningfully to environmental sustainability in OIC countries.